Кластеризація в мережах VEHICULAR AD-HOC networks - Соловйов, П. В. (ХНУРЕ, 2024)
The article analyzes the VANET technology and shows the problems that arise in the network. It is proved that the need to introduce a hierarchical network structure is aimed at effective network management. The basic and modified structures of the VANET network are analyzed. The influence of clustering on the effectiveness of collision prevention in a VANET is studied. The analysis showed that the use of clustering can significantly affect the number of potential collisions compared to the baseline scenario, which in turn will reduce the emergency situation on the roads and increase the efficiency of road traffic.
Keywords: VANET technology; VANET network